Excitation energies expressed as orbital energies of Kohn–Sham density functional theory with long‐range corrected functionals. Issue 14 (28th February 2020) - Hirao, Kimihiko; Chan, Bun; Song, Jong‐Won; Bhattarai, Kamala; Tewary, Subrata
Abstract: A new simple and conceptual theoretical scheme is proposed for estimating one‐electron excitation energies using Kohn–Sham (KS) solutions. One‐electron transitions that are dominated by the promotion from one initially occupied orbital to one unoccupied orbital of a molecular system can be expressed in a two‐step process, ionization, and electron attachment. KS with long‐range corrected (LC) functionals satisfies Janak's theorem and LC total energy varies almost linearly as a function of its fractional occupation number between the integer electron points. Thus, LC reproduces ionization energies (IPs) and electron affinities (EAs) with high accuracy and one‐electron excitation energies are expressed as the difference between the occupied orbital energy of a neutral molecule and the corresponding unoccupied orbital energy of its cation. Two such expressions can be used, with one employing the orbital energies for the neutral and cationic systems, while the other utilizes orbital energies of just the cation. Because the EA of a molecule is the IP of its anion, if we utilize this identity, the two expressions coincide and give the same excitation energies. Reasonable results are obtained for valence and core excitations using only orbital energies. Abstract : A simple and conceptual theoretical scheme is proposed for estimating one‐electron excitation energies using Kohn‐Sham solutions.